Adults with a child maltreatment history: Narratives describing individual strengths that promote positive wellbeing. (May 2023) - Schneiderman, Janet U.; Mennen, Ferol E.; Palmer Molina, Abigail C.; Cederbaum, Julie A.
Abstract: Background: Child maltreatment often has negative impacts, but some individuals have strengths that lead to better outcomes. Objective: Describe the narratives of adults who experienced childhood maltreatment, all of whom had positive psychosocial wellbeing at average age 18 years. Participants and setting: A purposive sample of 21 adults (mean age 27.8 years SD  = 1.0) who were part of a longitudinal study on the effects of childhood maltreatment. The sample was self-described as 85.7 % female, 14.3 % male, 42.9 % Black, 33.3 % Latinx, 19.0 % White, and 4.8 % multiracial. Methods: This descriptive qualitative study, which is part of a sequential mixed method study, used semi-structured interviews and a narrative analysis approach. Four coders completed: (1) initial reading of sample interviews (2) generating codes independently and discussion, (3) creating a codebook, (4) reviewing 10–11 transcripts each (5) reconvening to discuss/resolve differences in coding, (6) identifying themes. Results: There were four themes. The first theme was seeing oneself in a good light, highlighting self-worth and helper roles. The second theme, moving forward, included letting go of their past and a future orientation. Coping with life, the third theme, included boundaries for people around them, routines, and self-sufficiency. Meaning making, the fourth theme, included insights on the effect of their maltreatment and foster care, and reflections on appreciating life and adapting to changing circumstances. Conclusions: Findings describe varied strengths that promote positive functioning after childhood maltreatment. Study themes highlight how these strengths allow adults to make meaning of their experiences and move forward successfully in life.